2006
DOI: 10.1108/14720700610689603
|View full text |Cite
|
Sign up to set email alerts
|

Corporate social responsibility from a “stakeholder view” perspective: CSR implementation by a Swiss mobile telecommunication provider

Abstract: Purpose -The purpose of this research is to show how corporate social responsibility (CSR) is actually implemented and managed in business practice by a mobile communications provider in Switzerland. Based on this presentation the paper aims to analyze whether this implementation in the firm is consistent or not, to the responsibilities derived from the stakeholder view framework as it has been proposed by .Design/methodology/approach -The goal of this investigation is twofold. From a theoretical perspective, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 9 publications
0
24
0
Order By: Relevance
“…Sachs et al (2006) focused their analysis on Orange Communications in Switzerland and found that the firm devoted much attention to employees. They believe this to be the case because employees are both benefit providers/receivers and risk providers/receivers.…”
Section: Industry Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…Sachs et al (2006) focused their analysis on Orange Communications in Switzerland and found that the firm devoted much attention to employees. They believe this to be the case because employees are both benefit providers/receivers and risk providers/receivers.…”
Section: Industry Effectmentioning
confidence: 99%
“…Urgency is based on two characteristics; time sensitivity and importance of the claim to the stakeholder (Thorne, Ferrell, and Ferrell 2003). In addition, Sachs et al (2006) distinguish four categories of stakeholders as benefit providers/receivers and/or risk providers/ bearers. Stakeholders may be granted different levels of salience depending on the number of categories into which they fall.…”
Section: Literature Reviewmentioning
confidence: 99%
“…By using the matrix, we can provide useful information for management in decision making for both short-term and long-term in response with the interests of shareholders. Sachs, Maurer, Rühli, and Hoffmann (2006) argued that Carroll's (1979) model failed to reflect the real-world situation. The core value of stakeholder view framework is having clear understanding of property rights.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Aligned with this, we have adopted Sachs et al (2006) approach that aligns a stakeholder perspective of CSR and corporate governance. Viewing corporate governance through a stakeholder lens broadens traditional shareholder-centric and hub-spoke approaches to organisation-stakeholder relationships (Andriof et al 2002).…”
Section: Corporate Governance and Csr: A Combined Stakeholder Perspecmentioning
confidence: 99%